Factors That Influence the Improvement of Financial Performance of MSMEs With Religiosity and Financial Technology as Moderation - Surjadi, Merna; B.P. Simandjuntak, Johanes; Whittleliang Hakki, Tandry; Rosewita, Bella (Journal of Accounting and Finance Management, 2025)
This study uses primary data collected by distributing questionnaires to MSMEs in several major cities in Indonesia, including MSMEs in Jakarta, Denpassar, Bandung, Surabaya, and Medan. The results of this study are The Influence of Accounting Information Systems on the Financial Performance of Micro, Small and Medium Enterprises, The Influence of Financial Literacy on the Financial Performance of Micro, Small and Medium Enterprises, The Influence of Accounting Management Strategies on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Financial Technology as a moderating variable for the Influence of Accounting Information Systems on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Financial Technology as a moderating variable for the Influence of Financial Literacy on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Financial Technology as a moderating variable for the Influence of Accounting Management Strategies on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Religiosity as a moderating variable for the Influence of Accounting Information Systems on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Religiosity as a moderating variable for the Influence of Financial Literacy on the Financial Performance of Micro, Small and Medium Enterprises, The Role of Religiosity as a moderating variable for the Influence of Accounting Management Strategy on the Financial Performance of Micro, Small and Medium Enterprises.